A Conceptual and Technical Discussion on Digital Painting as New Media Art: Introducing Some Malaysian Works - Mumtaz Mokhtar (Journal of Visual Art and Design, 2013)
The revolution of media technology offers artists a lot of possibilities to create different art forms. The artist explored and manipulated different media to give different impact in their works since modernism and post modernism period. Malaysia as one of Asian country also committed to art development where artist explore various media in painting including conventional and technological media as well. Digital technology and art movement were developed in two separate segments. In fact, new media art does not establish in art history plot. Therefore, the word digital painting poses an ambiguity to describe its status. The convergence of scientific term and art term called digital painting will be discussed into two sections under conceptual issues and technical issues. In conceptual issues, digital painting will be linked to the ingredient and components of art including the artist, the form, the audience and its surrounding, the subject, and the content. This paper will also discuss what is behind digital painting which includes some technical issues including concept of digital image, the hardware and the software. This paper will confer some Malaysian digital paintings situation and scenario. Subsequently, it summarizes the core elements in digital painting to be implemented in further studies.